Green HRM : Sustainable Use Of Resources & Their Impact. - Keshtty, Priyadarshani Vinaykumar . (International Journal of Psychosocial Rehabilitation, 2020)
Green Human Resources Management (GHRM) termed as the set of policies, practices, and systems that stimulate a green behavior of a company’s employees in order to create an environmentally sensitive, resource efficient and socially responsible workplace for overall organization. Green HRM refered as growing role of sustainable development, its ecological aspect, in the development of a modern company competitive edge, leads to the popularization of the question of incorporating ecological practices into the area of human resource policy. To challenge and catastrophes climate change has brought, and threatens to bring into our world , sustainability strategies are growing fast within thousand companies .There no way of denying the importance that companies have in to fight to prevent the temperature of the Earth increasing 1.5º Celcius until the end of this century. Senior management is essential in a company’s execution of its sustainability management. Technology allows companies to become paperless and for HR this will start with newcomers. Offer-letters, credentials, CVs or recommendation letters can be used to archive employees’ documentation.CVs are mostly sent throughout the Internet, with no need of print that can be used with current employees’ health insurance or car contracts, salary or information on other benefits. The newcomers arrive at the office, induction programmes should be designed in such a way as to facilitate the integration of these new employees with the company’s culture of green consciousness. These programmes should also highlight the company’s concerns with environmental issues and the green actions being developed both inside the company and along its value-chain together with other stakeholders.